Synthesis and evaluation of antitumor activities of novel chiral 1,2,4-triazole Schiff bases bearing γ-butenolide moiety - Li, Xiang (Springer, 2012)
BACKGROUND: 1,2,4-Triazole derivatives have received much attention due to their versatile biological properties including antibacterial, antifungal, anticonvulsant, antiinflammatory, anticancer, and antiproliferative properties. 1,2,4-Triazole nucleus has been incorporated into a wide variety of therapeutically interesting molecules to transform them into better drugs. Schiff bases of 1,2,4-triazoles have also been found to possess extensive biological activities. On the other hand, γ-substituted butenolide moiety represents a biological important entity that is present in numerous biologically active natural products. RESULTS: We have described herein the synthesis of 12 hybrid 1,2,4-triazole Schiff bases bearing γ-substituted butenolide moiety. These compounds were synthesized by utilizing the tandem asymmetric Michael addition/elimination reaction as the key step. All the new compounds were evaluated for their in vitro anticancer activity. CONCLUSIONS: Tandem asymmetric Michael addition/elimination approach has offered an easy access to new chiral 1,2,4-triazole compounds 7a-7l. All these chiral 1,2,4-triazole derivatives exhibited good anticancer activities towards Hela. Of all the tested compounds, the chiral compound 7l with an IC(50) of 1.8 μM was found to be the most active.